Cultural memories and place-identity: a case study of Syrian refugees’ resettlement and acculturation strategies in Egypt - Fahmy, Randa (University of the Witwatersrand, Johannesburg, 2024)
Focusing on the Syrian refugees in Egypt—the aftermath of the 2011 public uprising, and the so called “Arab Spring”, or the “Jasmine Revolution”—this thesis explores the interaction of four main social factors influencing Syrian refugees place identity in the host country, Egypt. The first factor is the circumstances that caused the displacement of Syrians to become refugees in Egypt. The second factor is the refugees’ production of architectonic elements in the host country that are ideologically presumed to be ‘authentic’ architectural cultural heritage from their homeland. The presumed authentic architectural culture manifests as territorialisation in the host country for the protection of Syrian refugees’ identity. The third factor is the ‘globalisation’ forces that blend commercially inspired diverse trendy architectural styles into universal interchangeable consumables while ignoring contextual and cultural specificity. The fourth factor is the elucidation of what was realised when the three factors—the refugees, presumed authentic architectural culture, and globalisation forces—come together in the host country. Preliminary studies suggest that Syrian refugees maintain interactive tensions among the perceived original homeland architectural cultural identity, globalisation forces, and the necessity to modify the presumed original culture to adjust and settle in the host country. Examining the intersections of these four factors is the topic of this thesis. It is also observed that refugees tend to conceptualise authentic heritage ideology in placemaking to maintain an assumed cultural- identity in these globalising times of displacements and movements. Thus, in the effort to realise the assumed authentic architectural cultural heritage in the host country, Syrian refugees’ placemaking in Egypt defaults into another form of territorialisation that is inspired by architectural cultural memories from their homeland. Territorialisation disaggregates, personalises, and distorts the image of cultural identity of the places where refugees dream to be because it motivates them to be distinguished from their host culture while at the same time seeking to assimilate into the host country. This irony and the conflict of wanting to belong to the host country but, at the same time, wanting to be separate by retaining their Syrian identity, is the core of the study. Also, this thesis uses the architectural production of Syrian refugees in the host land, Egypt, in examining how architectural cultural memories are used for recreating personalised places of displaced groups. It is observed that the refugees present the personalized new creations in the host country as their “authentic” architectural culture purely on ideological bases.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy in Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Cultural-Memory; Refugees; Refugees of Arab Origin(s); Ideology of Cultural-Authenticity; Globalisation forces; Place-identity.; SDG-11: Sustainable cities and communities